A rare case of extraperitoneal gastrointestinal stromal tumor arising from kidney - D V Singh; Vinod Kumar; Ahmed Kamaal (Indian Journal of Urology, 2020)
Mesenchymal tumors of the gastrointestinal tract which arise from the interstitial cells of Cajal and express C-Kit protein or CD117 on immunohistochemistry are known as gastrointestinal stromal tumors (GISTs). Extraperitoneal GISTs (EGISTs) are rare tumors arising from the mesentery, omentum, or retroperitoneum. We report a case of a 52-year-old male who presented with a huge abdominal lump arising from the right renal capsule that was found to be EGIST on histopathological examination and immunohistochemistry.